TINGKAT KESEGARAN JASMANI MAHASISWA PRODI PENJASKESREK STKIP PARIS BARANTAI - Hasyim Hasyim; Jusran S (STKIP Paris Barantai, 2022)
This study aims to determine the level of physical fitness in students of physical education at STKIP Paris Barantai. This research is quantitative descriptive. The method used is a survey with data collection techniques using tests and measurements of the Indonesian Physical Fitness Level (TKJI) aged 16-19 years. The subjects in this study were students of physical education at STKIP Paris Barantai, totaling 28 people. The data analysis technique used descriptive analysis as outlined in the form of a percentage. Based on the results of the research and discussion, it was found that the level of physical fitness of the students of physical education at STKIP Paris Barantai was in the very good category, there were 0 boys (0%), 6 boys (21%) in the good category, 22 boys (79%) in the medium category, 0 sons (0%) in the poor category, and 0 sons (0%) in the very poor category. The results of this study can be concluded that the level of physical fitness in students of Physical Education and Health at STKIP Paris Barantai is in the medium category. Key words: the level of physical fitness, the students of physical education.